1982
DOI: 10.1038/bjc.1982.217
|View full text |Cite
|
Sign up to set email alerts
|

Early and late morphological changes (including carcinoma of the urothelium) induced by irradiation of the rat urinary bladder

Abstract: Summary.-Effects of X-irradiating the urinary bladder of female F344 rats with a single dose of 20 Gy were studied by light and electron microscopy. The animals were killed 1 week-20 months post-irradiation, and all tissues of the bladder wall were found to be affected by the irradiation.In the urothelium, damage was initially restricted to the basal cells but slowly extended to intermediate cells, and by 6 months post-irradiation the urothelium was focally hyperplastic. Twenty months post-irradiation, transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Chronic progressive changes in bladder compliance resulted in a reduction in absolute capacity data at all the different times of day as well as in a decrease in the amplitude of diurnal variations, indicating a higher absolute reduction in bladder capacity at times with normally high capacity. During this late response phase, which is associated with pronounced histological and cell kinetic changes [20], increased deposition of col lagen and ensuing fibrosis of the bladder wall [21] are like ly causes of decreased elasticity of the bladder wall. The organ may then be unable to respond to the factors nor mally regulating diurnal variations in capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic progressive changes in bladder compliance resulted in a reduction in absolute capacity data at all the different times of day as well as in a decrease in the amplitude of diurnal variations, indicating a higher absolute reduction in bladder capacity at times with normally high capacity. During this late response phase, which is associated with pronounced histological and cell kinetic changes [20], increased deposition of col lagen and ensuing fibrosis of the bladder wall [21] are like ly causes of decreased elasticity of the bladder wall. The organ may then be unable to respond to the factors nor mally regulating diurnal variations in capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The animal model used in this experimental study showed significant activation and de novo synthesis of TGF-1 following irradiation and surgery [32]. It has been shown that total reference doses between 30 and 50 Gy caused lesions in tissues that are comparable to those found in humans after radiotherapy [3]. Preresearch with a total reference dose of 30 Gy, 40 Gy, 50 Gy and fractionation of 3 ϫ 10 Gy, 4 ϫ 10 Gy, 5 ϫ 10 Gy, 10 ϫ 3 Gy, 10 ϫ 4 Gy was carried out to identify the fractionation model corresponding to the clinical situation [30].…”
Section: Discussionmentioning
confidence: 77%
“…The response of urothelial tissue to radiation is characterized by early edamatous changes, followed by proliferation and loss of differentiation . Edematous tissue changes explain the improvement of urinary incontinence for patients after prior TURP.…”
Section: Discussionmentioning
confidence: 93%
“…The response of urothelial tissue to radiation is characterized by early edamatous changes, followed by proliferation and loss of differentiation. 24 Edematous tissue changes explain the Impact of TURP on RT for prostate cancer improvement of urinary incontinence for patients after prior TURP. However, this improvement has not been observed in the patient group without prior TURP, with normal vascular function and compensation capacity.…”
Section: Discussionmentioning
confidence: 99%